(Re)estruturação urbana e o processo de gentrificação em Venda Nova Belo Horizonte/MG - Diniz, Luciano dos Santos (2015)
In order to strengthen the role of cities in the domestic economic environment national and ensure their integration into the global market, the modifying actions proceeded by the Government, in conjunction with private capital, not always broaden the citizens' right to the city. Sometimes such actions lead, albeit unintentionally, to the intensification of inequality, exclusion, and socio-spatial segregation of the poorest segments of the population. The objective of the research was to identify whether the interventions made by the Government in the North Section of the metropolitan region of Belo Horizonte, since 2005, have initiated the gentrification process of the study area Venda Nova. Specifically, it sought to identify the elements that characterize the gentrification process, understood as ennoblement/elitization of certain areas, with conceptual basis of national and international literature. Therefore, were researched the occurrence of land order changes; the changes in urban infrastructure, in the typology of buildings and in census indicators. For this purpose, in the present study, it was used a bibliographical, documental and survey research with older residents, recent residents and former residents that allowed knowing and evaluating the gentrification phenomenon in its temporality. The research has concluded that, in fact, the interventions proceeded by the government in the North Sector of the metropolitan region of Belo Horizonte have initiated the gentrification process of the study area, which is characterized by an active role of the Government; the reinvestment of public and private capital in the surrounding environment; changes in the order land; the transformation of the built environment; the reorganization of the social cartography of the area with the arrival of higher-socioeconomic-level residents; and finally, the indirect displacement of low-income residents